IMPACT OF IMPLEMENTING LABORATORY INFORMATION MANAGEMENT SYSTEMS (LIMS) ON IMPROVING DATA MANAGEMENT AND REPORTING - Mazen Abdulrahman Mohammed Alamer, Talag Mohammed H. Gafary, Rashad Ali Mohammad Refae, Khalid Mohammed Derbeshi, Ali Hassan Ali Arishi, Mohammed Yahya Jarradi Ammari, Abdulmajeed Ali Abdulqader Alaqi, ,; Ahlam Ibrahim Hadi Sowadi, Nadia Ali Qassim Juhynah, Amenah Mohammed Ahmed Bokar, Radha Mohammed Ali Makaramei, Amani Yahya E Hazmi, Waleed Abdulrahman Salem Alattas, Khalid Salem Alanazi, Sami Abdullah Alotaibi, (Chelonian Research Foundation, 2022)
Implementing Good Laboratory Practices (GLP) enhances the precision and accountability of findings in the field of health sciences research. Nevertheless, the adoption of these practices in research and academic labs may be hindered by reasons such as frequent staff turnover, inadequate resources, and insufficient training for management. The objective of this Scoping Review was to identify digital technologies used for the management of academic health sciences and experimental medicine labs, as well as their association with best practices. Using the PRISMA-ScR 2018 criteria, a search strategy was implemented up to April 2021 in the PUBMED, Web of Sciences, and Health Virtual Library databases. An evaluation of the chosen references was carried out, followed by the organization of data into a chart. The search found twenty-one acceptable papers, mostly from high-income nations, that discussed the creation and/or use of thirty-two electronic management systems. The majority of the studies focused on describing the features of the program. However, nine studies specifically assessed and addressed the effects on management, noting both enhancements in the workflow and limitations of the system during installation. Overall, the research indicates that there is a connection to various management challenges associated with GLP principles. To summarize, this analysis has shown that digital laboratory management systems have the potential to be valuable aids in adhering to the standards of good practices in experimental medicine and health sciences research, as new evidence continues to emerge. Keywords: scoping review; academic health centers; software; laboratory management.